1 − ( 1 3 ) 3 1 + ( 2 4 ) 9 1 − ( 3 5 ) 2 7 1 + …
If the above summation is equal to S , evaluate 1 0 0 × 3 S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It'd be better if gave a proof of that. The proof is simple though.
k = 0 ∑ ∞ ( k k + 2 ) x k = k = 0 ∑ ∞ ( 2 k + 2 ) x k = k = 0 ∑ ∞ 2 ! 1 ( k + 2 ) ( k + 1 ) x k
Differentiating twice the identity stated below w.r.t x gives us the closed form for the sum above.
k = 0 ∑ ∞ x k + 2 = 1 − x 1 − x − 1 ∀ x : 0 < ∣ x ∣ < 1
The problem posed is the sum stated at the top of this comment with x = ( − 3 1 ) which satisfies the convergence condition as 0 < ∣ ∣ − 3 1 ∣ ∣ = 3 1 < 1 .
Problem Loading...
Note Loading...
Set Loading...
Its just the binomial expansion of (1-x)^ -3 ..where x= -1/3.
Therefore S= (1+1/3)^-3 = (4/3)^-3 = (3/4)^3
So the required evaluation is 100 * (3/4 ) = 75 .